2018
DOI: 10.2139/ssrn.3114054
|View full text |Cite
|
Sign up to set email alerts
|

Tax Avoidance and Accounting Conservatism

Abstract: This study analyzes the relation between accounting conservatism, future tax rate cuts and countries' level of book-tax conformity. Firms have an incentive to increase conservatism in financial reporting when a tax rate cut is imminent to shift taxable income into the lower taxed future. Using a panel of firms across 18 countries from 1995 to 2010 I find that conditional conservatism is positively and significantly associated with future tax rate cuts when book-tax conformity is high. This effect is particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Hsieh et al [21] observed that firms with overconfident CEOs and CFOs were more likely to participate in tax avoidance activities. Reputation was another motivation for executives to use power to avoid tax, consistent with Bornemann's [22] research.…”
Section: The Literature On Corporate Tax Avoidancesupporting
confidence: 75%
“…Hsieh et al [21] observed that firms with overconfident CEOs and CFOs were more likely to participate in tax avoidance activities. Reputation was another motivation for executives to use power to avoid tax, consistent with Bornemann's [22] research.…”
Section: The Literature On Corporate Tax Avoidancesupporting
confidence: 75%
“…Jiménez-Angueira et al (2021) evidence that tax planning associated with unrecognized tax benefits (UTBs) increases the firm value when related to higher accounting conservatism. Furthermore, Bornemann (2018) documents that future tax cuts drive accounting conservatism, and this is more pronounced in countries with higher book-tax conformity (i.e., there is an association between book and tax income). Hellman (2008) argues for a strong link between accounting and taxation in code-law countries.…”
Section: Accounting Conservatism and Tax Aggressivenessmentioning
confidence: 99%
“…The negative association of the C-score and CETR corroborates the hypothesis of the study that, ceteris paribus, conditional conservatism is negatively associated with tax burdens. Bornemann (2018) conducted a study in Austria to analyse the relationship between accounting conservatism, future tax rate cuts, and countries' level of book-tax conformity using a panel of firms across 18 countries from 1995 to 2010. He used the C-score to measure conditional conservatism and book-tax conformity to measure tax avoidance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%